METAMORFOSIS KESADARAN ETIS HOLISTIK MAHASISWA AKUNTANSI IMPLEMENTASI PEMBELAJARAN ETIKA BISNIS DAN PROFESI BERBASIS INTEGRASI IESQ - Aji Dedi Mulawarman; Unti Ludigdo (Universitas Brawijaya, 2010)
The purpose of this research is to perform the deep meaning from implementation of Business Ethics and Profession Learning based on IESQ Integration (PEBI-IESQ). This PEBI-IESQ function is to instill two holistic ethical values awareness on accounting students. First, ethical awareness that has balance of intellectual, emotional and spiritual values; second, there must be an ethical values inside the accounting students when interact in an organization, and also inside the accounting system/science itself. Our Research, carried out in Accounting Department, Faculty of Economics, Brawijaya University. Using “methodological polytheism” (qualitative-quantitative interrelation) called “Extension” of “habitus” awareness concept in Bourdieu’s Generative Structuralism, to emancipate empirical-sociological dominated education towards metaphysics-sociological-spiritual enlightened education. The Result shows that, first, all the students (215) found an important common awareness, integrated intellectual-emotional-spiritual values. Second, 115 students (53,49%) found culminative awareness metamorphosis of “self” towards ultimate habitus that give the students trigger to be an ethical accountant and wishful to construct the new ethical accounting. Third, 79 students (36,74%) found middle awareness with prior habitus that give the students to be an ethical accountant and to implement more ethical accounting. Fourth, 21 students (9,77%) found unclear awareness with standard habitus that give the students to become an ethical accountant.